The strategy paradox : why committing to success leads to failure, and what to do about it - Raynor, Michael E. (New York : Currency Doubleday, 2007)
The purpose of this book is to describe how the strategy paradox can be resolved . In what follows , a new principle called 'requisite uncertainty and a new management tool called strategic flexibilty provides a way for managers to implement the kinds of strategies that can deliver outstanding results while maximising exposure to the vagaries of fate.
What strategy paradox? -- The best laid plans -- Who dares wins, or loses -- The limits of adaptability -- The limits of forecasting -- It's about time -- Making choices versus creating options -- Strategic flexibility -- What if?? -- Preparing for the unpredictable -- Reinventing strategy.
Includes bibliographical references and index.
opc 10/05/13
Loans
Keywords: Strategic planning; Uncertainty; Risk management